Creative encounters, appreciating difference: perspectives and strategies - Gill, Sam D. (Studies in body and religion, 2019)
Creative encounters, appreciating difference: an introduction -- Appreciating difference : encountering, moving, naming -- Moving beyond place -- Territory -- I don't want to be a mystic! : on self-moving and religious experience -- Not by any name -- Creations of encounter -- Mother earth and numbakulla -- Storytracking the arrernte through the academic bush -- Mother earth : an American myth -- Aesthetic of impossibles -- Myth and an aesthetic of impossibles -- Tomorrow's eve and the next gen study of religion -- Gesture -- Gesture posture prosthesis -- They jump up of themselves -- As prayer goes so goes religion -- Play -- No place to stand : Jonathan Z. Smith as homo ludens, the academic study of religion sub specie ludi -- To risk meaning nothing : Charles Sanders Peirce & the logic of discovery -- Creative encounters -- Creative encounters.